Hubungan Tingkat Kemandirian Activity of Daily Living (ADL) dengan Tingkat Kualitas Hidup Lansia di Desa Dukuhwaluh Kecamatan Kembaran Kabupaten Banyumas - Saputri, Amaliawati; Kurniawan, Wasis Eko; Sumarni, Tri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Various diseases related to aging are becoming more common among the elderly, which can affect their quality of life. One of the factors that affect quality of life is independence. Independence for the elderly to be able to fulfill basic human needs, it is very important for them to pay attention, receive instructions, and be guided in caring for themselves. This study aims to determine the relationship between the level of independence of Activity of Daily Living (ADL) with the level of quality of life of the elderly in Dukuhwaluh Village, Kembaran District, Banyumas Regency. Cross sectional design and descriptive correlation were used in this research strategy. A total of 79 elderly people became the sample size for the random sampling technique. WHOQOL-BREF and Barthel index were used as questionnaires. Using the spearman rank test in this study. The results showed that the level of independence of Activity of Daily Living (ADL) of the elderly in Dukuhwaluh Village, Kembaran District, Banyumas Regency mostly had an independent category as many as 63 respondents (79.7%). The level of quality of life of the elderly in Dukuhwaluh Village, Kembaran District, Banyumas Regency mostly has a good category as many as 57 respondents (72.2%). The Pvalue result is 0.001 <0.05 and the correlation coefficient is 0.371 based on statistical tests. The conclusion based on the results of the study, there is a fairly strong correlation between the level of independence of Activity of Daily Living (ADL) with the level of quality of life of the elderly in Dukuhwaluh Village, Kembaran District, Banyumas Regency.